Comparison of the Effectiveness of Circuit Training and Interval Training on the Physical Endurance of Basketball Athletes - Farrel Thouriq Adiyasa; Roy Januardi Irawan; Soni Sulistyarto; Afif Rusdiawan (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
Basketball is a team sport that requires physical, technical, and psychological abilities simultaneously. Improving aerobic endurance is essential for maintaining optimal performance throughout the game; therefore, selecting an appropriate training method is important. Interval training and circuit training are two commonly used methods to enhance aerobic endurance. This study aimed to compare the effects of interval training and circuit training on the aerobic endurance of basketball athletes at MAN 2 Mojokerto. This study employed a quantitative approach with a matching-only quasi-experimental design involving 20 male basketball athletes aged 16–18 years. Participants were divided into an interval training group (n = 10) and a circuit training group (n = 10). Aerobic endurance was measured using the Multistage Fitness Test (Bleep Test). Data were analyzed using descriptive statistics, paired-sample t-tests, and the Mann–Whitney U test. The results showed that both interval training and circuit training significantly improved aerobic endurance (p < 0.05). The interval training group demonstrated a slightly greater mean improvement than the circuit training group; however, the difference in improvement between groups was not statistically significant (p = 0.112). Therefore, both interval training and circuit training can be considered effective methods for improving the aerobic endurance of adolescent basketball athletes